2006
DOI: 10.1111/j.1467-9345.2006.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking literacy teaching with assessment: a continuing professional development initiative for secondary schools

Abstract: As part of a professional development initiative helping secondary school teachers use assessment data to guide their instruction, teachers in this study changed their knowledge, skills and dispositions. Over time, they were able to identify assessments, administer these assessments, interpret the results and plan instruction. As a result, the students who were tutored by these teachers increased their achievement compared with a control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…According to various studies done in assessment practices, inconsistencies have been discovered in the findings on the factors influencing university academic staff's assessment practices (Boud & Associates, 2010;Zhang & Burry-Stock, 2003;Eckert et al, 2006;O'Grady, 2006;Bloxham & Boyd, 2007;Fisher et al, 2006;Popham, 2009). Assessment practices inconsistencies among academic staff in universities have been linked to students' increased failure, poor academic accountability, and divergences in grades among students (Bloxham & Boyd, 2007;Gibbs, 2006;Ebersole, 2009;Benjamin & Klein, 2006;Haken, 2006).…”
Section: The Present Studymentioning
confidence: 99%
“…According to various studies done in assessment practices, inconsistencies have been discovered in the findings on the factors influencing university academic staff's assessment practices (Boud & Associates, 2010;Zhang & Burry-Stock, 2003;Eckert et al, 2006;O'Grady, 2006;Bloxham & Boyd, 2007;Fisher et al, 2006;Popham, 2009). Assessment practices inconsistencies among academic staff in universities have been linked to students' increased failure, poor academic accountability, and divergences in grades among students (Bloxham & Boyd, 2007;Gibbs, 2006;Ebersole, 2009;Benjamin & Klein, 2006;Haken, 2006).…”
Section: The Present Studymentioning
confidence: 99%
“…They found that the provision of active learning opportunities in TPD made teachers' use of new classroom practices increase. Fisher, Lapp, Flood, and Moore (2006) 21 described a CPD initiative that guided teachers' instruction by linking teaching and assessment. After this CPD, teachers improved their knowledge, skills, and dispositions, and they were able to apply what they learned from the CPD to improve their students' learning.…”
Section: B Cpd Evaluationsmentioning
confidence: 99%